Fearfulness: an important addition to the starter kit for distinctively human mind - Dwyer, D; Heyes, C (Cambridge University Press, 2023)
Grossmann's impressive article indicates that – along with attentional biases, expansion of domain-general processes of learning and memory, and other temperamental tweaks – heightened fearfulness is part of the genetic starter kit for distinctively human minds. The learned matching account of emotional contagion explains how heightened fearfulness could have promoted the development of caring and cooperation in our species.